Enterprise risk management and cost of debt: the moderating role of crisis - Wulan Rahmawati; Sylvia Veronica Siregar; Elvia R. Shauki; Viska Anggraita (Cogent Business & Management, 2024)
This study aims to investigate the relationship between enterprise risk management and cost of debt in the context of developing countries by considering the moderating role of the COVID-19 pandemic crisis period which is suspected to strengthen the negative association between these two variables. Using 310 non-financial sector companies listed on the Indonesia Stock Exchange for the period of 2018–2021 as samples, this study found that the implementation of effective risk management is associated with lower cost of debt charged by lenders. However, the association between these two variables was not visible during the COVID-19 crisis. These results are robust when sub-sample tests, assessment with alternative ERM measurements, and sensitivity test using the generalized method of moments (GMM) are performed. To the best of the authors' knowledge, this study is the first to address the direct relationship between enterprise risk management and external funding, especially cost of debt in the context of developing countries. In addition, this study is also the first to provide empirical evidence of the correlation between the COVID-19 pandemic and these two variables in the context of developing countries, specifically Indonesia.
Keywords: 650; Enterprise risk management; cost of debt; Covid-19; Indonesia